Tantangan Data Quality pada Pelaporan Penyakit Menular: Studi Kasus Pelayanan Publik Kesehatan di Indonesia - Hendry, Darell; Devina, Fakhira; Nabasya, Oristania Wahyu; Ruldeviyani, Yova (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Data management in the process of reporting infectious diseases in public health services presents a significant challenge. The quality of the generated reports is crucial as they are utilized for various strategic decision-making purposes. However, the successful management of data quality depends on understanding the existing reporting processes and the challenges faced. This study aims to explore the main challenges encountered during the COVID-19 reporting process, using a case study of public health services, and to identify the processes occurring in the field. Recommendations for practitioners are also provided. This research employed interview methods and analyzed them using thematic analysis, following the standards of the Consolidated Criteria for Reporting Qualitative Research (COREQ). Interviews were conducted with experts from public health centers and health departments in Indonesia. The challenges identified from 124 codes encompass issues related to data accuracy, data consistency, data timeliness, and data completeness. Recommendations have been formulated based on data management body of knowledge and critical success factors related to data quality